2010
DOI: 10.1510/icvts.2010.251041
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery or transsternal thymectomy in the treatment of myasthenia gravis?

Abstract: A best evidence topic in thoracic surgery was written according to a structured protocol. The question addressed was how video-assisted thoracoscopic surgery (VATS) compares to median sternotomy in the surgical management of patients with myasthenia gravis (MG)? Overall 74 papers were found using the reported search, of which 15 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 14 publications
4
60
0
9
Order By: Relevance
“…Advocates of single-port VATS have emphasized its benefits, including better cosmesis, less pain and faster recovery in the early postoperative period. These positive outcomes have also been observed in our limited experience (1,11,12).…”
Section: Discussionsupporting
confidence: 83%
“…Advocates of single-port VATS have emphasized its benefits, including better cosmesis, less pain and faster recovery in the early postoperative period. These positive outcomes have also been observed in our limited experience (1,11,12).…”
Section: Discussionsupporting
confidence: 83%
“…In the early 1990s, Roviaro (11) reported on video-assisted thymectomy. Comparing VATS and MS for the treatment of MG, it has been shown that VATS is typically associated with reduced blood loss and a shorter operative time and hospital stay, while VATS may also lower the incidence rate of postoperative complications by reducing tissue damage, postoperative pain, and the risk of infection (12,13). When comparing RATS (the newest MG surgical therapy) and MS for the treatment of MG, it has been demonstrated that RATS has favorable outcomes in terms of surgical complications and hospital stay (14).…”
Section: Discussionmentioning
confidence: 99%
“…6) In the present case, resection of the tumor through a cervical incision and subsequent video-assisted thoracoscopic extended thymectomy with the sternum-lifting method were performed because the patient had elevated AchR-Ab, although he lacked symptoms of MG. The outcomes of video-assisted thoracoscopic extended thymectomy have been reported to be comparable to those of trans-sternal extended thymectomy in patients with MG. 7) On the other hand, resection of the thymoma and extended thymectomy does not usually reverse the immunological abnormalities of GS. Therefore, regular follow-up with close attention to the development of infections is necessary.…”
Section: Ectopic Cervical Thymoma Accompanied By Good's Syndromementioning
confidence: 99%